Peran Homeschooling Terhadap Minat dan Bakat Anak Serta Kemampuan Bersosialisasi - Shakira, Bunga; Oktafia, Rezi; G, Gusmaneli (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Homeschooling is increasingly being recognized as an alternative educational option that offers flexibility and personalized learning experiences. This study aims to explore the benefits, challenges, and effectiveness of homeschooling within the context of Indonesian education. Data were collected using a qualitative approach, involving in-depth interviews and case studies with families practicing homeschooling. The findings reveal that homeschooling can enhance the quality of learning through tailored approaches to individual needs, albeit requiring high levels of commitment from parents and children. This research provides insights for families and policymakers in designing an inclusive and flexible education system.